Sistem Pengambil Keputusan Untuk Penentuan Penerima Bantuan Langsung Masyarakat PNPM Mandiri Menggunakan Simple Additive Weighting (Studi Kasus Kecamatan Ngadirojo Kabupaten Pacitan) - Elsen Ronando; Enny Indasyah (Jurnal Mantik Penusa, 2017)
Poverty is a major problem for developing countries, especially in Indonesian country. To decrease the level of poverty in society, it become the main work program of the current government. One of the work programs that have been done to reduce poverty was a direct assistance program for village’s communities. However, the existing direct assistance system is still manual and subjective. Thus, the distribution becomes inefficient and uneven. Based on this problem, this study aims to address the direct assistance problem to the community efficiently. A simple additive weighting method (SAW) was applied to analyze the determination of direct assistance for communities. The results of this research shows that the proposed method can sort receiver of direct assistance in the villages of Ngadirojo Pacitan based on priority scale. Keywords: Simple Additive Weighting, Direct Assistance, Ngadirojo